Identifying Technical Efficiency Differences between Online and Traditional Banking System in Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
Banking business has become very dynamic in recent days and has undergone rapid changes because of technological innovation, increased awareness and demand from customers, which makes the environment of the banking industry more complex and competitive. Currently, Banks are utilizing ICT in its each activity for better, error-free and prompt customer service, organized management decisions as well as managing risks. Among the banks operating in Bangladesh, Janata Bank PLC has been at the forefront of embracing digitalization and contributing to the country's overall digital transformation. The aim of this study is to analyze the theoretical foundations of bank efficiency, understand the measures of technical efficiency at the branch level briefly and find out the variables that affect the performance of the online banking system and traditional banking system in Janata Bank PLC. The data were collected from all the 909 branches of Janata Bank PLC. during the year 2019 and the sample bank was selected by using purposive sampling technique based on the availability of data and convenience of the study.  The DAE input-oriented analysis is employed to find out the technical efficiency of performance between online and traditional banking systems. However, comparing the performance of technical efficiency between online and traditional branches of Janata Bank PLC., it was found that traditional branch units were less potential than online branch units. Therefore, the findings suggest that the traditional branches will be more efficient by adopting new technology-based online services, as well as investing in new technologies to change the banking service quality.J Bangladesh Agril Univ 23(4): 524–531, 2025